1997
DOI: 10.1080/01904169709365300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfur nutrition on photosynthesis in cadmium‐treated barley seedlings

Abstract: The effects of sulfur (S) nutrition at 0.1 or 1 mM S on cadmium (Cd) toxicity measured by photosynthesis in barley (Hordeum vulgare L. cv. UC 476) seedlings were studied. Eight-day-old seedlings were treated with 25 µM Cd by adding cadmium chloride (CdCl 2 ) to the nutrient solution. Then photosynthetic carboxylation efficiency (ACi curve) and stomatal conductance of the primary and second leaves were measured at four and eight days after Cd treatment. Fluorescence parameters were measured every 24 h for eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…attained their g smax values when the value of C i was close or similar to what is expected under normal growth conditions (Chen and Huerta 1997).…”
Section: Effects Of CD and Si On Gas Exchange Parametersmentioning
confidence: 68%
See 1 more Smart Citation
“…attained their g smax values when the value of C i was close or similar to what is expected under normal growth conditions (Chen and Huerta 1997).…”
Section: Effects Of CD and Si On Gas Exchange Parametersmentioning
confidence: 68%
“…Cadmium-induced inhibition of growth has also been demonstrated to result from the accumulation of storage products at the expense of cell growth and elongation (Moya et al 1995;Verma and Dubey 2001). Furthermore, Chen and Huerta (1997) suggested that Cd-induced growth inhibition is due to an inhibition of photosynthesis. Thus, based on our results we suggest that the inhibition of growth due to low-level Cd-stress is most likely coupled to a reduction in photosynthesis (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Reduced photosynthesis under sulfur-deficient conditions was observed in barley (Karmaker et al 1991;Chen and Huerta 1997), rapeseed (Leoncini et al 1997), spinach (Dietz and Heilos 1990), soybean (Sexton et al 1997), and tomato (Xu et al 1996). S deprivation decreased the CO 2 assimilation rates in all the leaves of young wheat seedlings (Gilbert et al 1997).…”
mentioning
confidence: 99%
“…Cadmium-induced growth reduction might be explained on the basis of inhibition of carbon fixation due to a decrease in photosynthetic rate and chlorophyll content (Hattab et al, 2009). Cadmium in soils could induce water stress in plants by decreasing stomatal conductance and transpiration (Chen and Huerta 1997).…”
Section: Discussionmentioning
confidence: 99%